2016
DOI: 10.1073/pnas.1600567113
|View full text |Cite
|
Sign up to set email alerts
|

Conserved 33-kb haplotype in the MHC class III region regulates chronic arthritis

Abstract: Genome-wide association studies have revealed many genetic loci associated with complex autoimmune diseases. In rheumatoid arthritis (RA), the MHC gene HLA-DRB1 is the strongest candidate predicting disease development. It has been suggested that other immune-regulating genes in the MHC contribute to the disease risk, but this contribution has been difficult to show because of the strong linkage disequilibrium within the MHC. We isolated genomic regions in the form of congenic fragments in rats to test whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 51 publications
(75 reference statements)
2
35
0
1
Order By: Relevance
“…In our study, higher Ltb and Ncr3 expression and lower Lst1 expression correlate with reduced arthritis severity in rats (1). Following these findings, we compared expression of these genes in a cohort of patients with rheumatoid arthritis (RA) and healthy controls and found that the expression of LTB, LST1, and NCR3 was higher in RA cases, but patients with mild RA showed higher NCR3 expression and lower LST1 expression than patients with severe RA (1).…”
supporting
confidence: 59%
See 3 more Smart Citations
“…In our study, higher Ltb and Ncr3 expression and lower Lst1 expression correlate with reduced arthritis severity in rats (1). Following these findings, we compared expression of these genes in a cohort of patients with rheumatoid arthritis (RA) and healthy controls and found that the expression of LTB, LST1, and NCR3 was higher in RA cases, but patients with mild RA showed higher NCR3 expression and lower LST1 expression than patients with severe RA (1).…”
supporting
confidence: 59%
“…We previously identified a conserved 33-kb haplotype comprising five genes, lymphotoxin-α (Lta), Tnf, lymphotoxin-β (Ltb), leukocytespecific transcript 1 (Lst1), and natural cytotoxicity-triggering receptor 3 (Ncr3), in the MHC class-III region regulating arthritis in rats (1). In our study, higher Ltb and Ncr3 expression and lower Lst1 expression correlate with reduced arthritis severity in rats (1).…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Initially, genetic linkage analysis (Box 1) is performed to identify the many different QTLs that regulate various arthritis phenotypes, including disease onset and severity, and also subphenotypes, such as CD4:CD8 T-cell ratio, and the presence of α­ 1 -acid glycoprotein (a marker of the systemic inflammatory response) and of cartilage oligomeric matrix protein (a marker of cartilage destruction) (Kawahito et al, 1998; Lorentzen et al, 1998; Olofsson et al, 2003b; Remmers et al, 1996). The contribution of some of these QTLs to disease phenotypes has been reproduced in congenic strains (see Box 2) (Bäckdahl et al, 2003; Olofsson et al, 2003a; Remmers et al, 2002) and further analysed through the generation of smaller sub-congenic fragments, to narrow down the arthritis-associated loci (Haag et al, 2015; Lorentzen et al, 2007; Rintisch et al, 2010; Yau et al, 2016). The aim of this approach is to arrive at a genetic region that is linked to a disease but that contains a minimal number of genes, making it feasible to map and analyse different candidate genes and polymorphisms.…”
Section: Different Strategies Of Disease Gene Identificationmentioning
confidence: 99%